ANALYSIS OF COASTAL COMMUNITY CONSUMPTION IN BIREUEN DISTRICT - Mahyu, Danil (JURNAL KEBANGSAAN, 2018)
This study aims to determine and explain how Coastal Consumption in Bireuen District and know and explain what factors affect the Consumption of Coastal Communities in Bireuen District. Scope of research is Coastal Communities in Bireuen District. Total Population in this research is 8.995 KK, So sample in this research is taken by 1% from total head of Family that is 90 KK. The method used in sampling this research is Cluster Sampling Method. The results showed that simultaneously the variables of family members, education level, income and age significantly influence the consumption of coastal communities in Bireuen District. Partial research results proved that based on regression analysis results can be explained that the more number of family members owned by coastal communities, it will further increase the consumption of coastal communities. Then can be explained that the higher the education level of a person, it will increase the consumption of coastal communities. And regression analysis results can be explained that the higher level of income of coastal communities in Bireuen District, it will increasingly increase the consumption of coastal communities. Keyword: Consumption of Coastal Communities in Bireuen District Konsumsi Masyarakat, family members, education level, income and age